Pengembangan Model Pembelajaran Passing Bola Voli Berbasis Aplikasi Bagi Siswa SMP - Ijang Irpan Holiluloh; Akhmad Sobarna; Sumbara Hambali (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aimed to determine the development model, feasibility level, and effectiveness of application-based volleyball learning to improve students’ passing skills in junior high school. The research method used was research and development. The sample consisted of 1 teacher and 47 eighth-grade students. Data collection instruments included questionnaires, AAHPER face pass wall-volley test, and Brumbach forearm pass wall-volley test. Data analysis techniques included quantitative and qualitative descriptive analysis. The results showed a significant difference between pretest and posttest scores, indicating that the application-based learning model is effective in improving students’ volleyball passing skills. In conclusion, the application-based volleyball learning model developed through the ADDIE stages (analysis, design, development, implementation, and evaluation) is feasible and effective in improving students’ passing skills. Keywords: Application, Learning Model, Passing, Volleyball